Peluang bencana banjir pada saat hujan lebat dan sangat lebat di kawasan Pantura Provinsi Jawa BaratPeluang Bencana Banjir Pada Saat Hujan Lebat dan Sangat Lebat di Kawasan Pantura Provinsi Jawa Barat - Dimas Yudistira; Rheinhart Christian Hamonangan Hutauruk (Buletin GAW Bariri, 2021)
West Java Province is one of the areas with the potential for flooding. This is due to the topographical characteristics of the lowlands where there are many tributaries and the high population density which increases every year, causing damage to the ecosystem. One of the factors causing flooding is rainfall that is high above normal, so that the water diversion system consisting of natural rivers and creeks as well as the existing artificial flood drainage and canal systems is unable to accommodate the accumulated rainwater so that it overflows. Many factors cause rainfall in Indonesia to be above normal, one of which is due to the influence of the El Niño South Oscillation (ENSO) in this case La Niña. Anticipation of facing heavy rainy season due to La Niña needs to be increased, in accordance with the high threat of disasters. In this study, using the Conditional Probability method to see the chance of flooding in the northern region of West Java which consists of Bekasi, Karawang, Subang and Indramayu. The data used in the study were rainfall from 9 rain posts with a time span from 1981–2010. This research resulted in a potential flood opportunity value in Karawang regency 83.33% represented by the Purwakarta rain station during heavy rains, while in Subang district it showed a flood probability value of 66.67% represented by the Wanayasa rain post during heavy rains, for Bekasi district the opportunity value The resulting flood was 83.33% which was represented by the Mt. Mas that happened when it rained heavily.